Semar Pagulingan Tirta sari Gong Kebyar = Semar Pagulingan Tirta Sari In the Middle of Popularity of Gong Kebyar - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT This study aims to know the existence of Semar Pagulingan Tirta Sari, Puri Kaleran, Peliatan. It is to know and to express the reason and factors supporting the existence and performance in the middle of the popularity of Gong Kebyar music. The existence of Semar Pagulingan in Bali is reduced by the popularity Gong Kebyar music. It is indicated by the fusion of gamelan Semar Pagulingan becomes gamelan Gong Kebyar, the role of role Semar Pagulingan by Gong Kebyar, and the turning over some of sekaa Gong Kebyar. By expressing either the causes and factors that support the existence of Semar Pagulingan Tirta Sari, are hoped they can be the main material of study by other sekaa-spkaq Semar Pagulingan in developing art activities, especially in art music Semar Pagulingan. Gong Kebyar becomes guickly popular. One of the reasons is caused by the musical and social factors. Musically, the handling of Gong Kebyar has a lot of lively, restless, sheerful, and flare-up impressions. This kind of impressions becomes very popular and attracts the society's attention especially the youth. From the view of social factor Gong Kebyar has a flexible function. In other words, it means that this gamelan can be used for various purposes. The gap of life between Semar Pagulingan commonly in Bali and Semar Pagulingan in Puri Kaleran, Peliatan, is a phenomenon which is interesting to investigate. In this study, there are two ways in getting the data needed, namely, the field research and library research This study uses the musicological and anthropological approaches, as the main approaches, which are supported by the other social fields of study, such as sociology, history, and economics. Selcaa of Semar Pagulingan Tirta Sari is sekaa which is very popular among sekaa of Semar Pagulingan existing in Bali nowadays. Since this sekaa has